Tanzania : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper reviews economic developments in Tanzania during 1996-98. Both traditional and nontraditional exports increased sharply in 1995/96 and 1996/97 as agricultural and manufacturing production responded to the reforms; however, exports fell again in 1997/98, owing initially to drought and subsequently the floods associated with the El Nino phenomenon. The external position strengthened during the last two years as the deficit on the current account of the balance of payments (excluding transfers) declined and international reserves rebounded to the equivalent of three months of imports of goods and nonfactor services.